Gateway to Global Aging Data: Resources for Cross-National Comparisons of Family, Social Environment, and Healthy Aging. (18th June 2021) - Lee, Jinkook; Phillips, Drystan; Wilkens, Jenny; ,
Abstract: Objectives: The Gateway to Global Aging Data (Gateway; g2aging.org) is a data and information platform developed to facilitate cross-country analyses on aging, especially those using the international family of Health and Retirement studies. We provide a brief introduction to the Gateway to Global Aging Data, discussing its potential for cross-national comparisons of family, social environment, and healthy aging. Methods: We summarize the survey metadata, study characteristics, and harmonized data available from the Gateway, describing the population represented in each study. We portray cohort characteristics and key measures of health and social environment from 37 countries in North America, Europe, and Asia using harmonized data. Results: Significant cross-country heterogeneity was observed in many measures of family, social environment, and healthy aging indicators. For example, there was a threefold difference in coresidence with children, ranging from 14% in Sweden to over 46% in Spain and Korea in 2014. From 2002 to 2014, the difference between informal care receipt in individuals of low and high wealth decreased by 6% in the United States and remained unchanged in England. The percentage of individuals aged 50–59 living alone in 2012 varied 15-fold, from a low of 2% in China to a high of 30% in Mexico. Discussion: By partnering with nationally representative studies around the globe, the Gateway to Global Aging Data facilitates comparative research on aging through the provision of easy-to-use harmonized data files and other valuable tools.